Adoption of a Comprehensive Approach to Overcome the Challenges Involved in the Implementation of Social Accountability in Medical Education: A Brief Review - Saurabh RamBihariLal Shrivastava; Prateek Saurabh Shrivastava; Mayur Wanjari (Wolters Kluwer Medknow Publications, 2024)
In the field of delivery of medical education, social accountability envisages the responsibility of medical and healthcare institutions to meet the health-related needs of the communities in the catchment areas. The medical colleges that have integrated social accountability in their curriculum work with a goal to produce not only knowledgeable and skilled medical graduates but also those who are committed to the well-being of the entire community. The process of implementation of social accountability in medical education can have its own share of challenges. There is an immense need to plan and implement potential solutions for each of the identified challenges to ensure maximum benefit to the students, teachers, and community at large. In conclusion, social accountability in medical education has been associated with multiple benefits to all the involved stakeholders. This calls for the need to identify the challenges that can play their part in the successful implementation in medical schools and employment of appropriate measures to overcome them and move thereby bringing about a decline in health disparity.